A Mechanistic Study of the Stereochemical Outcomes of Rhodium‐Catalysed Styrene Aziridinations. Issue 2 (26th November 2019) - Azek, Emna; Spitz, Cédric; Ernzerhof, Matthias; Lebel, Hélène
Abstract: The stereoselective, rhodium‐catalysed aziridination of styrene derivatives with a chiral N ‐mesyloxycarbamate was found to be highly substrate dependent. A density functional theory (DFT) study is herein reported to elucidate the stereochemical outcome of the aziridination process. Rhodium acetate was initially used as a model catalyst, followed by computational studies conducted with Rh2 [( S )‐nttl]4 . Both singlet and triplet rhodium nitrene species were identified as intermediates affording concomitant concerted and radical pathways. In the latter case, the radical intermediate appears to undergo a direct ring closure via a minimum energy crossing point (MECP) between the triplet and closed‐shell singlet surfaces. Exceptionally for the m ‐Br‐styrene aziridination, an alternative radical pathway with a carbon‐carbon bond rotation was observed, accounting for the observed 74:26 mixture of diastereomers. The computational analysis also suggests little control of the metal nitrene conformation with Rh2 (OAc)4 with the chiral N ‐mesyloxycarbamate: two conformers were located affording two diastereomers of the aziridine and correlating our experimental results. On the other hand, only one conformer was found for the nitrene generated from the chiral N ‐mesyloxycarbamate and Rh2 [( S )‐nttl]4 . The so‐called "all‐up" conformer of Rh2 [( S )‐nttl]4 was not only the most stable metal nitrene species, but also afforded the lowest energy transition state. The calculated dr for p ‐Br‐styrene aziridination agrees with the observed experimental result. The combination of experimental and computational results offers a detailed mechanistic picture, providing insights for further catalyst development to enhance reactivity and selectivity. Abstract :